IL-10+ NK and TGF-β+ NK cells play negative regulatory roles in HIV infection - Yongjun Jiang (BMC Infectious Diseases, 2018)
Abstract Background Natural killer (NK) cells play cytotoxic roles by targeting tumor cells or virus infected cells, they also play regulatory roles by secreting cytokines and chemokines. Transforming growth factor (TGF)-β and interleukin (IL)-10 are important immunosuppressive cytokines potentially related to the immune dysregulation that occurs in the infection of human immunodeficiency virus (HIV). NK cells are an important source of TGF-β and a main early producer of IL-10 in response to viral infection. Here, we evaluated the percentages of IL-10+ and TGF-β+ NK cells in HIV-infected patients relative to healthy controls (HCs). Methods Study participants (n = 63) included 31 antiretroviral treatment (ART)-naïve HIV-infected patients, 17 ART-treated HIV-infected patients, and 15 HIV-negative HCs. Expression of IL-10 or TGF-β in NK cells was examined by flow cytometry, and the influences of recombinant IL-10 (rIL-10) or recombinant TGF-β (rTGF-β) on NK cell function were investigated in vitro. Results Compared with HCs, ART-naïve HIV-infected patients had increased percentages of IL-10+ (2.0% vs. 0.4%, p = 0.015) and TGF-β+ (4.5% vs. 2.1%, p = 0.022) NK cells, and ART-treated patients also had a higher percentage of IL-10+ NK cells (2.5% vs. 0.4%, p = 0.002). The percentages of IL-10+ and TGF-β+ NK cells were positively correlated (r = 0.388; p = 0.010). The results of in vitro experiments demonstrated that rIL-10 and rTGF-β inhibited NK cell CD107a expression (p = 0.037 and p = 0.024, respectively), IFN-γ secretion (p = 0.006, p = 0.016, respectively), and granzyme B release after stimulation (p = 0.014, p = 0.040, respectively). Conclusions Our data suggest that the percentages of IL-10+ or TGF-β+ NK cells are increased in HIV-infected patients, and that rIL-10 and/or rTGF-β can inhibit NK cell functions in vitro, providing a potential therapeutic target for strategies aimed at combating HIV infection.